Investasi di Pasar Modal Syariah Perspektif Maqasid (Literatur Review) - Lutfiah Effendi; M. Yoga Pratama Harahap; Muthia Hafsari Hsb; Ria Tifany Tambunan; Muhammad Ikhsan Harahap (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Halal and haram transactions in the capital market are only part of the picture; it is also important to consider how markets can be shariah-compliant—that is, how they can be used to further the Islamic economic mission—by Muslims. Especially in the investment sector. Millennials are currently experiencing a major shift in their prevailing investment motivation, moving away from viewing investment solely as a tool for material gain or higher levels of personal development to also seeing it as a path to spiritual fulfillment. Many people believe that the prevalence of speculation in traditional investment strategies has contributed to various global economic crises. In this case, we must pay close attention to Maqashid al-shariah which is an examination of Allah SWT's purpose in establishing law. The rule of law imposed on Muslim communities is an effort to improve their quality of life. In this case, it is practiced in the context of Islamic economics that all economic activities are prohibited.